An Uncommon Initial Presentation of T-Cell/Histiocyte-Rich B-Cell Lymphoma: Acute Renal Failure. (March 2020) - Filizoglu, Nuh; Ones, Tunc; Ozguven, Salih; Turoglu, Halil Turgut; Erdil, Tanju Yusuf
Abstract : Abstract: T-cell/histiocyte-rich B-cell lymphoma accounts for approximately 1% to 3% of all cases of diffuse large B-cell lymphoma, and involvement of the kidneys comprises a mere 1% of the total primary extranodal lymphomas. We present a case of T-cell/histiocyte-rich B-cell lymphoma who had acute renal failure at initial presentation with bilateral lymphomatous infiltration depicted on FDG PET/CT scan. Four months after the treatment, a repeat FDG PET/CT scan revealed complete resolution of the renal lesions, indicative of the complete remission for kidneys.